The Social History of a Genre: Kathas across Languages in Early Modern North India. (April 2017) - Orsini, Francesca
Tales are ubiquitous in the literary culture of pre-modern North India, as elsewhere, and they come in all shapes, languages and inflections. For this reason, tracking them allows us to travel into and across most of the milieux of this multilingual literary culture. But precisely because of their ubiquity, when we move from the micro level of individual texts to the macro level of literary culture and historical processes, it becomes difficult to say anything more than 'they were there, they circulated, they usually retold the same stories in new ways or mixed familiar elements to produce new narratives'. Yet if we pay precise attention to their articulation and re-articulation of cultural and social imaginaries, the particular linguistic textures and aesthetic emphasis, material form and evidence of patronage, the shifting extent of circulation and popularity, we can use the longuedurée history of the katha genre to illuminate the historical dynamics of cultural and aesthetic change in the region in ways that intersect, connect and question macro-historical narratives of dynastic and epochal change.